EVALUATION OF RESISTANCE AND GENE EXPRESSION OF BARRAMUNDI, Lates calcarifer POST-INFECTION OF NERVOUS NECROSIS VIRUS - Fitriyah Husnul Khotimah; Alimuddin Alimuddin; Dinar Tri Soelistyowati; Sri Nuryati; Ketut Sugama; Ahmad Muzaki; Indah Mastuti; Sari Budi Moria Sembiring; Ketut Mahardika; Harton Arfah; Haryanti Haryanti (Indonesian Aquaculture Journal, 2022)
The most common problem in barramundi Lates calcarifer seedling production is the high mortality (> 90%) caused by nervous necrosis virus (NNV) infection. This research aims to evaluate the resistance and gene expression of barramundi challenged by NNV. Two populations were used in this study, i.e., Australian, and Situbondo-originated barramundi populations. The immune-related gene expression levels in the liver, head of kidney, and spleen were observed at 48 and 96 hours after post-infection (hpi). Barramundi’s survival and blood parameters were evaluated post-NNV infection. The results showed that the highest survival was revealed in Situbondo’s barramundi (42.0±4.47%) compared to Australian barramundi (20.0±7.07%) and no mortality was observed in the control without NNV infection. The higher survival rate in barramundi from Situbondo was in line with the blood profile. The number of red blood cell from Situbondo barramundi post-NNV infection (ST) at 96 hpi was higher (P<0.05) than Australian barramundi post-NNV infection (AT). The number of white blood cell of ST at 48 hpi was higher (P<0.05) than AT, but started to decrease at 96 hpi in ST barramundi. The total white blood cell in AT barramundi increased from 48 to 192 hpi. TNFα and IL1-β gene expression levels were significantly higher in the liver, head kidney, and spleen of Situbondo compared to Australian barramundi at 48 hpi, while MHCIIα gene expression in Situbondo’s was significantly higher compared to Australian barramundi at 96 hpi. These results indicate the important roles of all the genes in the barramundi’s immune responses against viral infection. Based on the results of the research, Situbondo’s barramundi has the potential to be used as a candidate for generating broodstock of disease-resistant strain.